Layout placement optimization methods using repeated user interface sequence patterns for client applications. (July 2019) - Chung, Jihye; Hong, Seongjin; Kim, Youngbin; Kang, SJ; Kim, Changhun
We propose a method for automatically optimizing the layout placement of user interfaces in commercial applications. The proposed method suggests an optimal user interface component placement layout for an application by considering behavior cost, repeated user interface sequences, and preferred placement area. We used the Apriori algorithm and a genetic algorithm efficiently to optimize user interface component placement based on the evaluation of a keystroke-level model. We verified the effectiveness of the proposed method using a customizable user interface for three applications, namely, Adobe Photoshop, 3DS MAX, and the massively multiplayer online role-playing game "World of Warcraft." Our experimental results show that the proposed system can both reduce the behavioral cost of an application at the user level and enable efficient user interface usage by considering interrelationship patterns among user interface components.